6(1-4p)=-8(-4+4p)-2

Simple and best practice solution for 6(1-4p)=-8(-4+4p)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1-4p)=-8(-4+4p)-2 equation:


6(1-4p)=-8(-4+4p)-2

We simplify the equation to the form, which is simple to understand
6(1-4p)=-8(-4+4p)-2

Reorder the terms in parentheses
+(+6-24p)=-8*(-4+4p)-2

Remove unnecessary parentheses
+6-24p=-8+*(-4+4p+)-2

Reorder the terms in parentheses
+6-24p=+(+32-32p)-2

Remove unnecessary parentheses
+6-24p=+32-32p-2

We move all terms containing p to the left and all other terms to the right.
-24p+32p=+32-2-6

We simplify left and right side of the equation.
+8p=+24

We divide both sides of the equation by 8 to get p.
p=3

See similar equations:

| 61-3x=13-9x | | -6x-3.2=-3x+4.4 | | -9(6+n)=-54 | | -4.3+(-9.3)= | | 3x^2y+5y=2x | | v=(3.14)(36)(16) | | 3(2x-1)-6(x-4)=-9 | | -8(1-2k)=8(k-3) | | 46+2=3(5x+1) | | (x^4)-(10x^3)+(21x^2)+40x-100=0 | | 5+16z-3=9z+93-6z | | 49-2x=9-7x | | 5a=2a+7 | | x=1.4-(1.2x) | | X+6.5=9.7 | | 5+3x=-2x | | -3+6v=3(3v+4) | | 4(5x+3)-5(2x+1)=27 | | 4x+9=40-3x | | 3(3x+1)=39 | | 6a=6a+7 | | -38-8x=-3(-6+5x) | | 4+12x=4+x | | 2x^2y+xy-100=0 | | 4+x=3x-2 | | 3.2+6=6m-15 | | 5m=8m-15 | | -(r-5-8p)= | | 4M+3M=12 | | 8(5+13x)-(-2x+8)=32 | | -7x+2.3=7x-7.9 | | -14-(-3)= |

Equations solver categories